Efectos de la deficiencia de hierro en el funcionamiento intelectual - Pollitt, Ernesto (1991)
The purpose of this paper is to present a comparative analysis of the results of six researches in which the author has participated, about the relation between iron deficiency and intellectual performance. The researches were carried out in Egypt. U.S.A., Guatemala, Indonesia and Thailand, with pre-school and school children. Iron deficiency with anemia are among the two nutritional deficiencies of major prevalence in the wodd and it must be expected that the same goes for Peru. One of the causes of the low consuming of food rich in iron is that these are too expensive for groupa of low socioeconomic level. The comparative analysis shows consistent resulta in the six studies and that iron deficiency affects achievernent in cognitive processes tests and academic tests. Resulta also show that the effects are revenible when appropriate treatment is given. At the same time, the analysis shows that there is not enough evidence to infer that iron deficiency without anemia affects the intellectual quotient.